Immunotherapy in breast cancer - Marmé, Frederik (Oncology research and treatment, 2016)
The importance of the tumor microenvironment including immune cell infiltrates in breast cancer has long been recognized. Tumor-infiltrating lymphocytes are prognostic and predictive; however, their prevalence as well as their prognostic and predictive power are subtype-dependent and appear most prominent in aggressive subtypes like triple-negative and HER2-positive disease. The immune responses observed in many cancers are attracted by tumor-associated antigens and, as suggested by recent research, by neoantigens - immunogenic antigens encoded for by non-synonymous mutations. The appealing promise of cancer vaccines has been pursued in breast cancer for over 2 decades; however, despite much effort having been put into vaccine trials, their clinical benefit, with the exception of some encouraging preliminary results, remains disappointing. The main hurdles compromising the efficacy of these vaccination strategies are the difficulties to generate broad and robust immune responses as well as to overcome immune escape mechanisms. The remarkable efficacy of immune checkpoint inhibitors in melanoma and lung cancer has set the ground for a race in the clinical development of numerous agents targeting these immune escape mechanisms in many tumor entities. Early clinical data in metastatic breast cancer suggests at least some clinical activity. This review discusses the current status and future perspectives of immunotherapy in breast cancer.